THE CORRELATION BETWEEN LOW BIRTH WEIGHT AND STUNTING IN 2-5 YEARS OLD CHILDREN - Fionna Willa Hartantio; Benedictus Triagung Ruddy Prabantoro; Steven Wijono (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: The WHO defines stunting as a growth and development failure of infants and toddlers due to poor nutrition, especially in the first 1,000 days of life, so the child's height is too low for the age. Epidemiologic data shows the prevalence of stunting in children under five years in 2018 reached 30,8%. Since conception, growth, and development greatly affect babies' growth and development at birth and throughout their lives. Low birth weight indicates the fetus's growth and development since the period of conception is inhibited, which results in the non-optimal formation and maturation of the organs in infants, which can chronically appear as stunting. Purpose: This research aims to determine the correlation between low birth weight and stunting in children 2-5 years old. Method: This study uses an observational analytic method with a case-control study design and purposive sampling. There are 60 subjects in this study. Data used in this research were obtained from medical records. The WHO chart analyzed height. This research was analyzed with the Chi-Square test with the alpha standard value 1,96 (α=0,05). Result: There's a significant correlation between low birth weight and stunting in children 2-5 years old (P-value = 0,001, OR = 19,3). Conclusion: Low birth weight history significantly correlates with the incidence of stunting in 2-5 years old children.